HILANGNYA AKSES SUBSIDI PENDIDIKAN BAGI SEKOLAH ASING DI JEPANG (STUDI KASUS : SEKOLAH KOREA UTARA) - Anjani Tri Fatharini (HI 15 UMY 236, 2015)
*236 Since 2010 the Japanese government has provided High School Enrollment Support Fund. However, the government refuse to give it to North Korean schools. The reason behind this refusal can be explained through the concept of political system and hard power. In political system, interest group called Zaitokukai articulate their interest to not give North Korean School subsidy because they are not qualified. The Japanese government also make this refusal as its hard power. The aim of this article is to find out what is the reason behind Japanese government refusal to give high school support fund for North Korean schools.